Das fronteiras: mulheres, gestão quilombola e gestão escolar no quilombo-ribeirinho de Alegre - Januária - MG - Gilmara Silva Souza (2017)
Starting from the historical and active process of invisibility and silencing suffered by quilombola communities, as a result of logics of oppression, such as the structural and institutional racism of the Brazilian State, stands out the struggles for recognition and access to social rights, especially for basic education that these communities undertake. In this process of struggle, memories are requested and visited, reflections on the trajectories of comings, goings, returns and transits in other lands (from the present and the past) are connected to the process of building the identity of who one is. This dissertation presents experiences and reflections that emerged from the encounter between black women and quilombolas from the north of Minas Gerais and another black woman, here as a researcher and that comes from the capital. The objective of this work was to understand how the quilombo of Alegre, in Januária (MG), builds the internal management processes of the community and to know how these are connected to the struggle for recognition with the public power. Based on an ethnographic, black feminist, quilombola, theoretical-methodological path, accompanied by the epistemologies of the South, the functioning of community management practices carried out by a group of women from the Quilombola Association, and the relationship of this group management with the school management experience present in the quilombo. We verified that the set of community management practices led by quilombo women makes life work within the community, based on three elements: the collective and interested participation of the other quilombolas; the union to carry out activities in favor of the collectivity; and collective care in different situations, such as not having an overload of activities on a person, and to avoid isolation and material and symbolic precariousness in the neighboring family. From the school management practices observed in the field, we found that the school does not work against the logic of the quilombola community, in opposite, in many moments we observe the effort of managers and teachers to carry out the meeting between school and community knowledge. In this sense, it opens up the possibility of quilombola school management, present in the community, to work from a logic of coexistence. The management of coexistence, which we call it, refers to the collective involvement to recognize the existence of other logics and forms of management, to mediate divergences and be open to learning and teaching together with the management of the community.